Memories of maternal upbringing could influence self-injurious behaviors in adolescents with diagnosis of eating disorders. - García, Ana Rosa (2022)
Objective: To explore the perceived parental rearing behavior in adolescents diagnosed with an eating disorder, and to identify eventual differences with altered eating and self-injurious behaviors. Material and methods: A total of 45 adolescents diagnosed with some eating disorder (11 diagnosed with anorexia nervosa, 23 with bulimia nervosa and 11 with binge eating disorder), recruited from the outpatient and hospitalization areas of the Juan N Navarro Children’s Psychiatric Hospital, were included. Results: It was found that the greater the memories of favoritism (r = 0.41, p-value = 0.005) or rejection (r = 0.36, p-value = 0.016) by the father, the higher the scores on the Eating Attitude Scale. Differences were also found in the mother’s warmth dimension, between the adolescents who presented self-injuries (mean = 39.6, de = 11.3) and those who did not present them (mean = 47.4, de = 8.8) (t =-2.6, value p = 0.015). Conclusions: Adolescents with a diagnosis of eating disorders presented differences in their perception of parental rearing, a factor that may decisively influence the manifestation of other psychopathological behaviors.